Effectiveness of individualized breastfeeding counseling during the dyad’s stay in rooming-in: a randomized, multicenter, open and parallel study - Mariana Torreglosa Ruiz; Elisa da Conceição Rodrigues; Marialda Moreira Christoffel; Cynthya Viana de Resende; Michele Curcino Cavalcanti; Marianne Guterres Ferreira; Jéssica Aparecida da Silva; Karine Emanuelle Peixoto Oliveira da Silva; Monika Wernet; Ana Letícia Monteiro Gomes; Maria Beatriz Guimarães Raponi; Jacqueline Faria de Oliveira; et al. (International Breastfeeding Journal)
Abstract Background Breastfeeding counseling is a proven strategy to protect and promote breastfeeding, as evidenced by numerous studies. However, there is limited research on its application during the dyad’s stay in rooming-in and its impact on the duration of exclusive breastfeeding. This study aims to evaluate the effectiveness of individualized counseling during the dyad’s rooming-in period and its role in maintaining exclusive breastfeeding until the sixth month of life, compared to standard care. Methods This randomized, multicenter, parallel, and open clinical trial was conducted at two Brazilian university hospitals. A total of 102 primiparous women, who had conditions and intentions favorable to breastfeeding, were enrolled between December 2023 and April 2024. Following hospital discharge, participants were followed up via telephone until the child reached six months of age, with the study concluding in October 2024. Participants were randomly assigned to one of two groups. The intervention group received two to four breastfeeding counseling sessions during their hospital stay, while the control group received standard institutional care. Both groups were provided with educational materials on the benefits of breastfeeding and information on where to seek help if complications arose. During the telephone follow-ups, outcomes were measured without any additional interventions. The primary outcome measured was the exclusive breastfeeding rate since birth to the sixth month. Results A total of 97 breastfeeding women completed the follow-up, forming the sample for analysis. Compared to the control group, women who received counseling were more likely to maintain exclusive breastfeeding at the fourth month (27/48 (56.2%) vs. 15/50 (30.0%), Prevalence Ratio = 1.88 (Confidence Interval 95% 1.15, 3.07) and the sixth month of the child’s life (27/47 (57.4%) vs. 12/50 (24.0%), Prevalence Ratio = 2.40 (Confidence Interval 95% 1.38, 4.16). Conclusion Breastfeeding counseling during the dyad’s stay in rooming-in was effective in maintaining exclusive breastfeeding until the child’s sixth month of life. Trial registration UTN: U1111-1284-3559 / RBR-4w9v5rq (2023-03-20).